Is there a causal relationship between exchange rate volatility and unemployment? - Alexander Jung (Intereconomics, 1996)
In his article on “Germany's Stake in Exchange Rate Stability” (INTERECONOMICS, September/October 1996), Daniel Gros recently wrote that, as he sees it, the exchange rate volatility of the D-Mark against the other European currencies has a causal impact on the German unemployment rate. In the following it is examined whether Granger causality tests support this view and whether it is possible to infer from this that the establishment of a monetary union in Europe will contribute to a significant easing of unemployment problems.
Keywords: 330